Pengembangan Media Pembelajaran Flashcard Pada Materi Sistem Ekskresi Kelas VIII Di SMP Negeri 3 Lolofitu Moi Tahun Pelajaran 2020/2021 - Kadini Kurniawati Halawa; Hardikupatu Gulo (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2023)
This study aims to determine the feasibility of the content/material, the feasibility of designing the Flashcard learning media by experts, to determine the practicality of the Flashcard learning media product and to determine the effectiveness of the Flashcard learning media on the excretory system material on student learning outcomes. This type of research is a research development using the Borg and Gall development model. The product trial was conducted in class VIII of SMP. The data collection instrument used a validation questionnaire, student response questionnaires, learning outcomes tests, and observation sheets. The result of the development is in the form of Flashcard learning media on the excretory system material. The results of the assessment of the feasibility level of content/material by lecturers are 91% with a very valid category, by subject teachers it reaches 95% with a very valid category. The results of the feasibility assessment by design experts obtained 100% with a very valid category. The results of the assessment of the level of practicality of using Flashcard learning media on the excretory system material obtained a percentage of 86% in the very practical category. The results of the assessment of the effectiveness of Flashcard media on the excretory system obtained completeness of 90% with a high category.